Effect of Malaria on Hematological Profile in Medical Unit-2 of Chandka Medical College Larkana - Iqra Hyder Khokhar, Bashir Ahmed Shaikh, Imdad Ali Ansari, Siraj Ahmed Channa, Saad Ali Ansari, Ali Rohail (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To see effects of malaria on haematological profile and to see the difference of changes due to malaria on hematological profile in both males and females. Study Design: Case control Place and Duration of Study: Medical unit-2 Department of Chandka Medical College, Larkana from 1st June 2022 to 30th November 2022. Methodology: Eighty seven patients of malaria and 80 without malaria were enrolled. A 3% Giemsa staining technique was applied for processing and staining of the films. Parasite density /ml blood was assessed. The blood samples taken from all participants were analyzed through proper quality assurances. The hematological profile included white blood cell counts (WBC), hemoglobin measurements (Hb), percentage of monocytes (MON%), percentage of lymphocytes (LYM%), percentage of neutrophils (NEUT%) as well as red blood cell distribution width (RDW-CV), and also the platelet counts (PLT). Results: Malaria had an impact on the hemoglobin levels. Among our patients, 73.5% showed mild anemia, 9.1% had moderate anemia, and 14.9% were diagnosed with severe anemia. Females were found to be more affected than males. The sensitivity and specificity of the study was estimated for all the hematological profiling and it was found that White blood cells, monocytes as well as hemoglobulin were very sensitive and specific predictors for malaria presence. Conclusion: Hemoglobulin levels, white blood cells count as well as platelets count are decreased significantly in malarial cases. Keywords: Malaria, Anemia, Thrombocytopenia, Hematological profile, Rapid acting ICT method, Plasmodium